THE ETHNICITY VIEW IN KHALED HOSSEINI’S THE KITE RUNNER AND PAULO COELHO’S THE ALCHEMIST (COMPARATIVE LITERATURE STUDY) - Islam, Aang Fatihul (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2015)
This article is concerned with ethnicity view in two novel namely Khaled Husain?s The Kite Runner and Paulo Coelho The Alchemist by using comparative literature approach. The problems which are proposed are (1) How are the ethnicity view in  The Kite Runner by Khaled Hosseini and  The Alchemist by Paulo Coelho?, and (2) What are the similarities and the differences of the ethnicity view in  The Kite Runner by Khaled Hosseini and  The Alchemist by Paulo Coelho?. To answer the problems, the researcher applies comparative literature theory and ethnicity theory and. In this study, the researcher employs a qualitative approach because several typical characteristics of qualitative are present in this study. In collecting the data the researcher uses the following procedures are used: (1) Selecting the novel, (2) reading the novel deeply, (3) selecting element of novels contain of ethnic view. After analyzing, the researcher finds After analyzing the two novels, it can be concluded that both of them have similarities and also differences.  The similarities are both of novels same contain one of the conceptions driven by Marx is the primacy of the economic base over the cultural and thus superstructure. The ethnics who have economic power will control other powerless. The Kite Runner and The Alchemist clearly describe that phenomenon. The facts that people are honored because of their status and wealth are true. The tribal wars will produce the winner that has economic power for the weapons and so on. The groups of different culture are rooted economically. When once they win the tribal war by economic power, they will oppress the other ethnics which powerless in economy. In fact thus condition describe in both of novels. The differences both of those novels are: in The Kite Runner the ethnic?s sentimentalism of the powerful economics (higher structure) is stronger, meanwhile in The Alchemist the sentimentalism of the powerful economics (higher structure) is lower. Although both of them were describe of the power of economic to oppress the poor tribal.